2005
DOI: 10.1073/pnas.0500112102
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline analogue-regulated transgene expression in Plasmodium falciparum blood stages using Toxoplasma gondii transactivators

Abstract: Genetic manipulation has revolutionized research in the Apicomplexan parasite Plasmodium falciparum, the most important causative agent of malaria. However, to date no techniques have been established that allow modifications that are deleterious to bloodstage growth, such as the disruption of essential genes or the expression of dominant-negative transgenes. The recent establishment of a screen for functional transactivators in the related parasite Toxoplasma gondii prompted us to identify transactivators in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 23 publications
0
90
1
1
Order By: Relevance
“…Regulated transgene expression has also been described in P. falciparum, in which a tetracycline analog is used to repress transactivated gene expression 27 . Combining our integrase system with these other techniques offers the prospect of developing efficient methods for complementation and change or loss-of-function studies.…”
Section: Discussionmentioning
confidence: 99%
“…Regulated transgene expression has also been described in P. falciparum, in which a tetracycline analog is used to repress transactivated gene expression 27 . Combining our integrase system with these other techniques offers the prospect of developing efficient methods for complementation and change or loss-of-function studies.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a system for conditional gene expression in T. gondii (Meissner et al, 2002), also applied recently to P. falciparum (Meissner et al, 2005), has provided a means to study the function of essential genes in apicomplexan parasites. In the second successful application of this system we have shown directly that TgAMA1 functions in host cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The two artificial transactivators functioning in T. gondii and P. falciparum correspond to a short stretch of rather hydrophobic amino acids. Neither transactivators function in HeLa cells, underlining the differences between the transcription machinery in apicomplexans and higher eukaryotes [65]. This new system led to the generation of the first conditional knockout for an essential gene with no apparent reversion effect and operates on the parasites in the animal model [64].…”
Section: Experimental Approaches and Tools Developed To Regulate Genementioning
confidence: 99%
“…Further characterisation of these transactivators revealed that they do not function in HeLa cells but can activate transcription in P. falciparum [65]. This restricted range of activity suggests that considerable differences exist between the core transcription machinery of these protozoa and other eukaryotes.…”
Section: The Basic Machinery Of Transcription In Apicomplexamentioning
confidence: 99%